2013
DOI: 10.4161/org.27213
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and electrostatics play active role in neuronal differentiation processes on flexible conducting substrates

Abstract: This commentary discusses and summarizes the key highlights of our recently reported work entitled "Neuronal Differentiation of Embryonic Stem Cell Derived Neuronal Progenitors Can Be Regulated by Stretchable Conducting Polymers." The prospect of controlling the mechanical-rigidity and the surface conductance properties offers a unique combination for tailoring the growth and differentiation of neuronal cells. We emphasize the utility of transparent elastomeric substrates with coatings of electrically conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…To investigate the role of type IV collagen in septation, we used an epithelial–mesenchymal co-culture model of alveolar morphogenesis [ 50 ]. This model produces peaks of mesenchymal cells covered by an epithelial lining.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the role of type IV collagen in septation, we used an epithelial–mesenchymal co-culture model of alveolar morphogenesis [ 50 ]. This model produces peaks of mesenchymal cells covered by an epithelial lining.…”
Section: Resultsmentioning
confidence: 99%
“…This model produces peaks of mesenchymal cells covered by an epithelial lining. The central core of mesenchymal cells closely resembles the myofibroblasts seen during alveolar septal development in vivo [ 50 ]. When MRC-5 fetal mouse mesenchymal cells were co-cultured with human A549 epithelial cells, septal-like formations appeared after 4–5 days and reached their maximum after 7 days (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the transplantation of cardiomyocyte patches can improve cardiac function after a myocardial infarction. 20,22,36 Rather than serving a therapeutic role, the microvessel patches in the present study could be combined with a cardiomyocyte patch to provide rapid blood flow to the implanted heart patch. This could allow for the implantation of larger patches and higher numbers of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In general, polymer surfaces with appropriate mechanical attributes such as adhesive strength, microtexture and nanotopography, surface wettability and stiffness are conducive for anchoring neuronal cells. 2,3 The electronic characteristics of certain conjugated polymers have also been used for sensing and stimulating neuronal activity. [4][5][6][7] The optoelectronic properties of these materials have recently been utilized as active triggers for neuronal stimulation.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%